EKSISTENSI LPP RRI MATARAM BERDASARKAN TEORI NICHE - Andi Tamrin (ORASI: Jurnal Dakwah dan Komunikasi, 2019)
AbstractThe level of competition of radio stations in NTB in the past few years has increased considerably with the presence of private radio. LPP RRI Mataran as a government radio, so naturally it must be able to compete and at the same time maintain its existence as a public broadcasting institution. This research uses descriptive qualitative research methods. By using Niche theory, LPP RRI Mataram can compete, while at the same time being able to maintain its existence as a public broadcasting institution because it can fulfill three major components to be able to compete with other industries. The three components are capital, advertisers who can support the survival of LPP RRI Mataram, namely from the state budget and regional budget. types of content, pro1, pro2, and optimize audio and video streaming technology resources and RRI Play, beyong. types of audience, the entire NTB community.